Analysis of Thermal Properties on Backward Feed Multieffect Distillation Dealing with High-Salinity Wastewater - Jianliang Xue; Qinqin Cui; Jie Ming; Yu Bai; Lin Li (Journal of Nanotechnology)
Theoretical investigations on thermal properties of multieffect distillation (MED) are presented to approach lower capital costs and more distillated products. A mathematical model, based on the energy and mass balance, is developed to (i) evaluate the influences of variations in key parameters (effect numbers, evaporation temperature in last effect, and feed salinity) on steam consumption, gained output ratio (GOR), and total heat transfer areas of MED and (ii) compare two operation modes (backward feed (BF) and forward feed (FF) systems). The result in the first part indicated that GOR and total heat transfer areas increased with the effect numbers. Also, higher effect numbers result in the fact that the evaporation temperature in last effect has slight influence on GOR, while it influences the total heat transfer areas remarkably. In addition, an increase of feed salinity promotes the total heat transfer areas but reduces GOR. The analyses in the second part indicate that GOR and total heat transfer areas of BF system are higher than those in FF system. One thing to be aware of is that the changes of steam consumption can be omitted, considering that it shows an opposite trend to GOR.